2016
DOI: 10.1002/cpdd.252
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the Long‐Acting Basal Insulin LY2605541 in Subjects With Varying Degrees of Renal Function

Abstract: The pharmacokinetics of LY2605541 (basal insulin peglispro), a novel long‐acting basal insulin analogue, was evaluated in 5 groups of subjects with varying degrees of renal function based on creatinine clearance: normal renal function (>80 mL/min), mild renal impairment (51–80 mL/min), moderate renal impairment (30–50 mL/min), severe renal impairment (<30 mL/min), or end‐stage renal disease (ESRD) requiring hemodialysis. Serial blood samples for pharmacokinetic analyses were collected up to 12 days following a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…These results suggested that hydrodynamic size and not molecular weight was also the prominent determinant of glomerular filtration for BIL, since the molecular weight of BIL is much lower than that of albumin (66 kDa) and is not filtered by the glomerulus under normal physiological conditions. The observations noted in the 5/6 nephrectomized rats were later confirmed in humans with varying degrees of renal impairment …”
Section: Receptor Binding Pharmacology and Mechanism Of Action Of Bilmentioning
confidence: 71%
See 1 more Smart Citation
“…These results suggested that hydrodynamic size and not molecular weight was also the prominent determinant of glomerular filtration for BIL, since the molecular weight of BIL is much lower than that of albumin (66 kDa) and is not filtered by the glomerulus under normal physiological conditions. The observations noted in the 5/6 nephrectomized rats were later confirmed in humans with varying degrees of renal impairment …”
Section: Receptor Binding Pharmacology and Mechanism Of Action Of Bilmentioning
confidence: 71%
“…The observations noted in the 5/6 nephrectomized rats were later confirmed in humans with varying degrees of renal impairment. 34…”
Section: Introductionmentioning
confidence: 99%
“…It showed that clearance of lispro protamine was significantly reduced in renal impairment, but with no effect on the clearance of BIL keeping its glucose-lowering properties. This observation occurred because of BIL’s increased hydrodynamic size, which reduced renal ultrafiltration [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…In patients undergoing dialysis, BIL did not appear to be significantly eliminated, less than 25%. They concluded BIL was well tolerated in patients with different degrees of renal function and with no need to reduce the dose [ 14 ].…”
Section: Methodsmentioning
confidence: 99%
“…LY2605541 has a lower binding affinity for the insulin receptor and insulin‐like growth factor‐1 receptor than lispro, and a lower mitogenic potency than human insulin . The half‐life is 24–45 h and duration of action exceeds 36 h , and are unaffected by renal impairment . Animal studies suggest that LY2605541 may have a hepatoselective action on glucose metabolism [].…”
Section: New Prolonged Insulin Analoguesmentioning
confidence: 99%